2020
DOI: 10.1093/bjsw/bcaa164
|View full text |Cite
|
Sign up to set email alerts
|

Negotiating Reunion in Intercountry Adoption Using Social Media and Technology

Abstract: This article focuses on how intercountry adoptees use social media and technology to negotiate and facilitate reunion with their birth families. The qualitative data were drawn from in-depth, semi-structured interviews with eleven adoptees who were internationally adopted to Ireland and have contact with their birth families using social media and technology. The findings from this interpretivist study demonstrate that social media and technology have significantly transformed and can now play a central role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The third major finding is related to the unique role that American Indian family members, relatives, and tribe play in calling home their fostered/adopted relatives. Although previous research suggests that birth siblings can facilitate contact between the adopted relative and the family of origin (Shier, 2021), our findings expand upon such findings to include other family members as well. Participants in this study were sought and found by their birthparents, siblings, and extended family members.…”
Section: Discussionsupporting
confidence: 45%
See 3 more Smart Citations
“…The third major finding is related to the unique role that American Indian family members, relatives, and tribe play in calling home their fostered/adopted relatives. Although previous research suggests that birth siblings can facilitate contact between the adopted relative and the family of origin (Shier, 2021), our findings expand upon such findings to include other family members as well. Participants in this study were sought and found by their birthparents, siblings, and extended family members.…”
Section: Discussionsupporting
confidence: 45%
“…Historically, the practice of adoption was guarded by privacy and anonymity, but such protections cannot be guaranteed given technological advances in social media and ancestry DNA testing. Research suggests that searching can be facilitated through the internet, social media, and DNA databases (Baden et al, 2021; Child Welfare Information Gateway, 2018; Fischer, 2002; Haralambie, 2013; Shier, 2021). Registries have been established to assist adopted individuals and their families of origin in reconnecting and some even hire private investigators to assist in the search (Child Welfare Information Gateway, 2018; Fischer, 2002; Haralambie, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Such openness in adoption communication facilitates contact with the birth families; however, there may be risks involved when contact, especially virtual, occurs without any adoption agency or social worker mediation. Virtual contact is not seen as a replacement for ‘real’, face-to-face contact but as a positive way of supplementing existing relationships, and it is valued more if adoptive parents support it (Shier, 2021). Within India’s closed adoption system, this type of virtual contact is not possible.…”
Section: Challenges To the Digital Systemmentioning
confidence: 99%